1943
DOI: 10.1002/jctb.5000620202
|View full text |Cite
|
Sign up to set email alerts
|

Solanine, glycoside of the potato. Lits isolation and determination

Abstract: The method finully devised \\*:IS t,iisctl on the ~irctniso tlint it \viw hest, to iissunio thirt t'cle tleuitnitccl sulphuric ricitl ahonltl tic as conccntrnterl 11s possible, i.b., 43.5:(, II,sO, (&,) olitninnble wlien the feed is prclientcd nnd tho losses w e 11s stiitctl, 20% of tho stcnni input. Then, by cletcrniining stcnni!feed rntios for vnrious vrilncs of vnponr conipouitions, rising cold feet1 of tho given conqiosition ant1 innking out, lient. bnlniiccs using the nictliods iilrently describctl,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1943
1943
1994
1994

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…It is of interest to note that Rooke and his co-workers (24) have stated that ninety minutes is -required for maximum color density to be reached, which contrasts sharply with the find¬ ings in the present work. After several tests, all of which conformed to the curve shown in Figure 2, xo { rx/ nXvX-ii: v ::■:…”
Section: Rooke and Co¬contrasting
confidence: 98%
See 1 more Smart Citation
“…It is of interest to note that Rooke and his co-workers (24) have stated that ninety minutes is -required for maximum color density to be reached, which contrasts sharply with the find¬ ings in the present work. After several tests, all of which conformed to the curve shown in Figure 2, xo { rx/ nXvX-ii: v ::■:…”
Section: Rooke and Co¬contrasting
confidence: 98%
“…Rooke, et al, (24) said that the method of extraction of Bomer and Mattis, and also the modification of Conner, which necessitated the use of a large quantity of raw material, were found to give a sticky, semi-colloidal precipitate of solanine, difficult to filter and purify.…”
Section: Rsmmentioning
confidence: 99%
“…The FETAX solution (including all controls) used for that experiment was also adjusted to pH 6.9, which is within limits set by the ASTM (1991). We have previously showed that -chaconine and -solanine are soluble 0021-8561/94/1442-1511$04 in FETAX solution at these concentrations (Friedman et al, 1991;Rooke et al, 1943). Additional studies using HPLC to measure concentrations in solutions confirmed the solubilities of the hydrolysis products at the concentrations used.…”
Section: Methodsmentioning
confidence: 71%
“…Intensive investigation during World War II led to a modification of Pfankuch's (1937) analytical method (Rooke et al, 1943). Dabbs and Hilton (1953) developed a shorter method for extraction and analytical determination of solanine.…”
Section: Introductionmentioning
confidence: 99%